Health-Care Utilization Due to Suicide Attempts Among Homeless Youth in New York State. Issue 8 (12th February 2021) - Sakai-Bizmark, Rie; Kumamaru, Hiraku; Estevez, Dennys; Marr, Emily H; Haghnazarian, Edith; Bedel, Lauren E M; Mena, Laurie A; Kaplan, Mark S
Abstract: Suicide remains the leading cause of death among homeless youth. We assessed differences in health-care utilization between homeless and nonhomeless youth presenting to the emergency department or hospital after a suicide attempt. New York Statewide Inpatient and Emergency Department Databases (2009–2014) were used to identify homeless and nonhomeless youth aged 10–17 who utilized health-care services following a suicide attempt. To evaluate associations with homelessness, we used logistic regression models for use of violent means, intensive care unit utilization, log-transformed linear regression models for hospitalization cost, and negative binomial regression models for length of stay. All models adjusted for individual characteristics with a hospital random effect and year fixed effect. We identified 18, 026 suicide attempts with health-care utilization rates of 347.2 (95% confidence interval (CI): 317.5, 377.0) and 67.3 (95% CI: 66.3, 68.3) per 100, 000 person-years for homeless and nonhomeless youth, respectively. Length of stay for homeless youth was statistically longer than that for nonhomeless youth (incidence rate ratio = 1.53, 95% CI: 1.32, 1.77). All homeless youth who visited the emergency department after a suicide attempt were subsequently hospitalized. This could suggest a higher acuity upon presentation among homeless youth compared with nonhomeless youth. Interventions tailored to homeless youth should be developed.